Student evaluations: Pedagogical tools, or weapons of choice? - Warwick Fisher; John Orr; John Page; Alessandro Pelizzon; Helen Walsh (Legal Education Review, 2020)
In this paper, we survey the recent literature of student evaluation surveys ('SETs') in the university sector, in so doing identifying a number of diverse issues that this literature reveals, and contextualising its general findings to the teaching practices of a regional Australian law school.